2002
DOI: 10.1002/glia.10056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolactin on intracellular calcium concentration and cell proliferation in human glioma cells

Abstract: Prolactin (PRL) has several physiological effects on peripheral tissues and the brain. This hormone acts via its membrane receptor (PRL-R) to induce cell differentiation or proliferation. Using reverse transcription-polymerase chain reaction (RT-PCR) combined with Southern blot analysis, we detected PRL-R transcripts in a human glioma cell line (U87-MG) and in primary cultured human glioblastoma cells. These transcripts were deleted or not in their extracellular domains. We examined the effects of PRL on intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 75 publications
4
34
0
Order By: Relevance
“…It is possible that this response also involves prolactin-induced activation of phosphoinositol-3 kinase and production of a range of inositol phosphate molecules (54). Similar prolactin-induced increases in intracellular Ca 2ϩ are also seen in glial cell lines (16,17) and neurons (29) that endogenously express the PRL-R. Hence, there is precedence for both rapid stimulatory and inhibitory actions of prolactin, and it is conceivable that either response could be induced, depending on the physiological state of the cell.…”
Section: Discussionmentioning
confidence: 89%
“…It is possible that this response also involves prolactin-induced activation of phosphoinositol-3 kinase and production of a range of inositol phosphate molecules (54). Similar prolactin-induced increases in intracellular Ca 2ϩ are also seen in glial cell lines (16,17) and neurons (29) that endogenously express the PRL-R. Hence, there is precedence for both rapid stimulatory and inhibitory actions of prolactin, and it is conceivable that either response could be induced, depending on the physiological state of the cell.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, many hormonal changes occur following a first pregnancy, including a long-term lowering of levels of prolactin, estradiol, and androgens, and long-term higher levels of estriol. 32,44 -47 Prolactin has been shown to stimulate cell proliferation in cultured astrocytes and glioma cells, 48,49 , and it is conceivable that higher prolactin levels in nulliparous women may promote tumor growth.…”
Section: Discussionmentioning
confidence: 98%
“…For example, it has also been shown that calcium signaling is required for cell cycle progression from the G1/S phase through to mitosis (Hazelton et al, 1979;Tupper et al, 1980). Mitogenesis is accompanied by an increase in intracellular Ca 2 þ , so modifying intracellular Ca 2 þ alters proliferation and mitogenesis (Enomoto et al, 1998;Ducret et al, 2002).…”
Section: Discussionmentioning
confidence: 99%